Penggunaan Ayat-Ayat Al-Qur’an dalam Ritual Rebo Wekasan Studi Living Qur’an di Desa Sukoreno Kec. Kalisat Kab. Jember - Rohmah, Umi Nuriyatur (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2018)
This article highlights about using Qur‟anic verses in the society‟s ritual called Rebo Wekasan in Sukoreno. Rebo Wekasan is the annual ritual that celebrated by Sukreno‟s people. This ritual is celebrated on the last Wednesday of Shafar. This ritual aims refusing the unlucky things that believed sent down on that day. This ritual usings some Qur‟anic verses, when praying tola‟ bala‟ and making the holy water. This article focuses on practicing and meaning of using Qur‟anic verses in Rebo Wekasan. This article used descriptive qualitative methods with etnograph‟s approach using Karl Manheim‟s sociology of science theory. This articles shows that there are some surahs and verses of Qur‟an that used in Rebo Wekasan when praying tala‟ bala‟, i.e.: Surah al-Kausar, al-Ikhlas}, al-Falaq, and al-Nas. When making the holy water the verses that used are Yasin verse 58, al-S{affat verse 130 – 131, al-Zumar verse 73, al-Ra‟d verse 24, and al-Qadr verse 5. Based on Mannheim‟s theory,There are three meanings of using the Qur‟anic verses in this ritual, those are; objective as a tradition, expressive as refusing unlucky things (bala‟), and documenter as a culture